Fatigue Life Prediction of Two-Stroke Free Piston Engine Mounting Using Frequency Response Approach - M. M., Rahman; R. A., Bakar; A. K., Ariffin; Ummu Kulthum, Jamaludin; C. H. C., Haron (EuroJournals Publishing, Inc., 2008)

(untitled)
This paper describes a vibration fatigue analysis techniques to predict the fatigue life using the frequency response approach. The life prediction results are useful for improving the component design at a very early development stage. The finite element modeling and frequency response analysis have been performed using the finite element analysis software. In addition, the fatigue life prediction was carried out using both the time domain and frequency response methods. From the results, it is observed that the Dirlik method gives the best comparable results pseudo-static time domain approach with the frequency response techniques. This paper also describes how this technique can be implemented in the finite element environment to rapidly identify critical areas in the structure. This approach is capable of determining premature products failure phenomena.